Outcome of labor in vertex malposition in Cameroon - Nkwabong, Elie; Mba, Marie Foe; Fomulu, Joseph Nelson (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vertex malposition is associated with increased maternal and neonatal adverse effects, but its magnitude has not been well established in sub-Saharan women. This study aimed at evaluating labor outcome in cases of Vertex Malposition (VM) in Cameroon. Methods: This prospective cohort study was conducted in the University Teaching Hospital of Yaoundé (Cameroon) from March 1st, 2013 to February 28th, 2014. Women carrying singletons with or without VM in labor were monitored during labor. The main variables recorded included the duration of the second stage of labor, mode of delivery, birth weight and neonatal wellbeing. Data of women with VM were compared to those of women without it. Fisher’s exact test and t-test were used for comparison where appropriate. P<0.05 was considered statistically significant. Results: A total of 100 women were recruited in each group. There was no difference in the mean birth weights (P=0.56). VM was significantly associated with prolonged second stage of labor (RR 12.1, 95%CI 4.4-33.1), cesarean section (RR 12.6, 95%CI 5.3-30), instrumental delivery (RR 7.7, 95%CI 2.6-22.3), episiotomy (RR 6.2, 95%CI 2.8-13.7) and neonatal death (RR 8, 95%CI 1.01-62.7). Conclusions: VM is associated with increased maternal and neonatal adverse effects. Hence, delivery should be carried out in settings where cesarean section, instrumental delivery and neonatal resuscitation can rapidly be performed.